Niemcy w polskiej kulturze i myśli politycznej od schyłku XVIII w. do wybuchu II wojny światowej - Maciejewski, Marek (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The article describes the shaping of the stereotype of a German and Germany among Poles from losing the independence due to the third partition of the Polish Commonwealth in 1795 until the next loss of independence caused by the aggression of the Third Reich and the Soviet Union on Poland in 1939. During that period of around 150 years Polish opinions on Germans were influenced by various factors and circumstances: historical, political, social, cultural, ethical, aesthetic, etc. All those factors constituted a premise for the emergence of the usually negative and often simplified stereotype of Germans among different political and cultural Polish circles, characterized by a strong antipathy towards that nation, which was reciprocated by Germans. This stereotype was often an expression of the fear felt by the majority of Poles towards Germans, based on the perception of various dangers economic, military, cultural, etc. coming from this source. Many Poles perceived Germans particularly Prussians during that period as nationalists attempting to gain hegemony not just over Poles, mercilessly focused on fulfilling their national interest and discountingthe needs of other nations. The representatives of this nation were considered to be brutal, simple-minded, conceited and sometimes even intellectually challenged. Nevertheless, there were sometimes indications pointing out some positive traits of this nation: the love of order, the willingness for hard work, the will to maintain discipline. The negative stereotype of a German became particularly strongly fixed after the establishment of the united German Reich in 1871, especially after the seizure of power by the Nazis. Within this stereotype, positive evaluations outweighed negative assertions only during two historical periods: during the November Uprising and soon after its fall and during the Springtime of the Peoples in the mid-19th century.
Keywords: Niemcy; Polska kultura; polska myśl polityczna; historia